2017
DOI: 10.1080/02699052.2017.1341644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concomitant mild traumatic brain injury on resuming work after suffering from an isolated limb fracture: A cohort study

Abstract: This study shows that mTBI increases work disability by preventing working-age individuals from rapidly returning to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…43 These findings are in opposition to another study that found women who experienced mTBI and concomitant limb injury took a greater time to RTW than men. 44 Together, these findings support consideration of sex as an important factor that should be included in the treatment, management, and RTW components of mTBI protocols.…”
Section: Preinjury Risk Factors In the Work-related Mtbi Populationmentioning
confidence: 65%
See 2 more Smart Citations
“…43 These findings are in opposition to another study that found women who experienced mTBI and concomitant limb injury took a greater time to RTW than men. 44 Together, these findings support consideration of sex as an important factor that should be included in the treatment, management, and RTW components of mTBI protocols.…”
Section: Preinjury Risk Factors In the Work-related Mtbi Populationmentioning
confidence: 65%
“…This outcome has been attributed to aspects of workplace culture, as workers in supportive, female-dominated workplaces experienced a more positive RTW, whereas those in workplaces composed of predominantly male workers experienced greater RTW issues 43 . These findings are in opposition to another study that found women who experienced mTBI and concomitant limb injury took a greater time to RTW than men 44 . Together, these findings support consideration of sex as an important factor that should be included in the treatment, management, and RTW components of mTBI protocols.…”
Section: Preinjury Risk Factors In the Work-related Mtbi Populationmentioning
confidence: 77%
See 1 more Smart Citation
“…RTW was used in this study to reflect potential impact of HO development on functional outcome as it is known to be a good marker of recovery (Clay et al, 2010). Information on RTW was collected in the context of a previous study conducted by our group using the same sample (see Jodoin et al (2017b) for more details). Statistical analyses were performed using IBM SPSS software version 24 (Armonk, NY, United States).…”
Section: Methodsmentioning
confidence: 99%
“…MTBIs account for approximately 70–90% of all TBIs sustained and are frequent among patients who suffered from fractures, with an incidence rate estimated at 23% (Cassidy et al, 2004; Jodoin et al, 2016). Although considered the mildest form of TBIs, a growing body of evidence shows that concomitant mTBI can have a significant impact on recovery in patients with fractures, highlighting the importance of considering the interaction between these two injuries (Jodoin et al, 2017a, Jodoin et al, 2017b). To our knowledge, the association between mTBI and HO has not been investigated.…”
Section: Introductionmentioning
confidence: 99%